(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article presents important information about the formation of ideological immunity to destructive information. Ideological immunity refers to the methods and technologies used to support information against foreign ideas based on information selection. The article describes the methods of dealing with destructive information and the importance of forming ideological immunity. This article would be a good supplement to a book or journal article with information about the role and importance of ideological immunity in information security.